Experimental study on aerodynamic admittance of twin-box bridge decks. Issue 198 (March 2020) - Wang, Junxin; Ma, Cunming; Jing, Hongmiao; Pei, Cheng; Dragomirescu, Elena
Abstract: The current study attempts to investigate the characteristic of aerodynamic admittance of twin-box bridge decks via wind tunnel test. Pressure measurement has been carried out on three twin-box bridge models and one closed-box bridge model, for two different turbulent flow-fields. The aerodynamic admittances of those bridge models and the buffeting force coherences along the spanwise direction are obtained to clarify the difference between twin-box bridge deck and conventional closed-box bridge deck in unsteady aerodynamic force, and it is found that the aerodynamic admittance of twin-box girders at low reduced frequencies is significantly higher than that of the conventional closed-box girder, the coherence of fluctuating force on twin-box girders is lower than that for a conventional closed-box girder due to the existence of the central gap. The distributions of the fluctuating pressure on bridge models are presented and discussed, which reveal that the three-dimensional effect of the incident wind velocity depends not only on the ratio of turbulence integral scale to the width of the bridge deck, but also on the flow separation pattern. Finally, empirical models for determining the fluctuating force coherence and aerodynamic admittance of twin-box bridge decks are proposed based on in-depth data analysis and are proved to be effective for fitting the experimental data, while the fitting parameters can be applied to flow-fields with different turbulence integral scales. Highlights: Pressure measurement has been carried out on three twin-box bridge models and one closed-box bridge model, for two different turbulent flow-fields. Empirical models have been proposed for determining the ﬂuctuating forces coherence and aerodynamic admittances of twin-box bridge decks. Clariﬁcations are made regarding the differences between twin-box girder and conventional closed-box girder in forces coherence and aerodynamic admittance. This work discusses the ﬂuctuating forces acting on the twin-box girders in detail, which can provide a further understanding on aerodynamic admittance of bluff bodies.